Fault Detection & Classification in UPFC Integrated Transmission Line Using DWT - Sanjay Kumar Mishra; Sarat Chandra Swain; Loknath Tripathy (Institute of Advanced Engineering and Science, 2017)
Fault detection and classification in UPFC (Unified Power Flow Controller) integrated transmission line using single terminal based DWT (Discrete Wavelet Transform) is proposed. The current is extracted from the sending end bus and processed through wavelet transform to evaluate the spectral energy (SE) using db4 mother wavelet. Three level decomposition is framed to extract the fundamental frequency component from non-stationary signal, considering sampling frequency of 2kHz system. The fundamental frequency component of respective phase currents are used to compute SE at sending end. The SE of individual phase current is the key factor for deciding the fault pattern detection and classification. The advantage of using this it requires less cost and protect entire transmission line with minimal fault detection time. The various types of fault (L-G, L-L, L-L-G, L-L-L) are simulated by considering the parameter like fault resistance, source impedance, fault inception angle, multi-location fault, reverse power flow and UPFC system parameter. The scheme works reliable and efficient to detect and classify the fault within a cycle of sample period 40 or a cycle of time period 20ms compared to other conventional relaying scheme.